P050 Serum adropin levels in patients with Crohn's disease. (25th January 2019) - Zivkovic, P M; Tadin Hadjina, I; Rusic, D; Vilovic, M; Supe-Domic, D; Martinovic, D; Puljiz, Z; Tonkic, A; Bozic, J
Abstract: Background: Crohn's disease is a chronic inflammatory condition that primarily affects the gastrointestinal tract, with high possibility of systemic complications. Adropin is a novel discovered protein highly expressed in various organ systems that has an important role in energy homeostasis, metabolic control and intercellular communication. Adropin could be involved in the pathogenesis of number of diseases, according to the fact that different studies connected low adropin levels with metabolic syndrome, insulin resistance, coronary disease and heart failure. The main aim of this study was to compare serum adropin levels in patients with Crohn's disease and matched control subjects. Furthermore, additional goal was to investigate relationship between adropin and other standard biochemical parameters, and anthropometric measurements as well. Methods: In this study, 40 patients with Crohn's disease were enrolled (23 males and 17 females), as well as 40 age- and gender-matched control subjects. Serum adropin levels was measured by ELISA kit (Phoenix Pharmaceuticals), while other biochemical parameters were determined with standard laboratory procedures. Detailed anamnestic data and anthropometric measurements were taken from each participant. Results: Crohn's disease group had significantly lower serum adropin levels when compared with controls (2.13 ± 0.47 vs. 3.02 ± 0.55 ng/ml; p = 0.001). Regarding other biochemical parameters, there was no statistical significance in concentrations of glucose, total cholesterol, HDL, LDL and triglycerides between study and control group, while CRP levels were significantly higher in Crohn's disease group (20.12 ± 18.36 vs. 1.78 ± 1.56 mg/l; p = 0.001). Adropin showed significant positive correlation with both LDL ( r = 0.373, p = 0.014) and HDL ( r = 0.341, p = 0.023) concentrations, while significant negative correlation was found between adropin and CRP ( r = −0.368, p = 0.019). Conclusions: Our study demonstrated lower serum adropin levels in patients with Crohn's disease in comparison to controls. It is possible that adropin has a role in the complex pathophysiology of Crohn's disease. However, more investigations are necessary for further clarification of that connection.